The effects of working and employment conditions on the health status among the salaried population. An approaching according to Welfare Regimes in Europe - Merino i Noé, Jordi (Papeles de Europa, 2017)
This article brings in a proposal of confluence in one multilevel model of some studies proposed by different authors in the debate about different welfare models and conditions of employment as social determinants of health in Europe. Beginning with the results of the V European Working Conditions Survey, the primacy of working conditions, influence of the unemployment rate variation, social expenses and poverty threshold were noticed as associated factors with the perceived health state. Also, a considerable difference was seen depending on the regimes, indicating risk factors in the Mediterranean and Eastern Europe models for both sexes and in the Anglo-Saxon model for women. The characteristics of different regimes could have a mediating function of health state of the working population in Europe.
Keywords: Social Welfare; Working Conditions; Self-perceived-health; Multilevel modeling; social determinants of health